Null Mannheim curves in the Minkowski 3-space E13 (vol 35, pg 107, 2011) - Oztekin, Handan; Ergut, Mahmut (Tubitak Scientific & Technological Research Council Turkey, 2013)
In this paper, Theorem 3.2 and Proposition 3.2 in the paper which is cited in the title are corrected.